Comparison of Three Serologic Tests for the Detection of Anti-Coxiella burnetii Antibodies in Patients with Q Fever - França, Danilo Alves de [UNESP]; Mioni, Mateus de Souza Ribeiro [UNESP]; Fornazari, Felipe [UNESP]; Rodrigues, Nássarah Jabur Lot [UNESP]; Polido, Lucas Roberto Ferreira [UNESP]; Appolinario, Camila Michele [UNESP]; Ribeiro, Bruna Letícia Devidé [UNESP]; Duré, Ana Íris de Lima; Silva, Marcos Vinicius Ferreira; Richini-Pereira, Virgínia Bodelão; Langoni, Helio [UNESP]; Megid, Jane [UNESP] (MDPI, 2023)
The performance of a commercial immunofluorescence assay (IFA commercial), an in-house immunofluorescence assay (IFA in-house) and an indirect enzyme-linked immunosorbent assay (ELISA) were evaluated in the detection of antibodies anti-C. burnetii in the serum of Q fever patients and persons without the disease. For the study, seropositive and seronegative samples for Q fever (n = 200) from a serum bank of the Instituto Adolfo Lutz in Brazil were used. Commercial IFA was considered in this study as the gold standard for diagnosing Q fever. The in-house IFA demonstrated good agreement with the commercial test, showing high sensitivity (91%) and specificity (97%) compared to the gold standard, with a Kappa coefficient of 0.8954. The indirect ELISA test showed lower agreement with the gold standard, showing low sensitivity (67%), although the specificity of the technique was high (97%) and the Kappa coefficient was moderate (0.6631). In-house IFA is an excellent alternative for diagnosing Q fever.
Keywords: acute disease; ELISA; humans; immunofluorescence; Q fever; serodiagnosis